Screening and Application of SSR Markers for Identification of Ploidy in Oncorhynchus mykiss - Haibing MA; Tianqing HUANG; Gefeng XU; Enhui LIU; Wei GU; Gaochao WANG; Fuyuan GUO; Fulin DONG; Longhua ZHENG; Lili ZHANG; Zaisheng JIANG; Bingqian WANG (Progress in Fishery Sciences, 2024)
Rainbow trout (Oncorhynchus mykiss) is one of the world's most widely farmed cold-water economic fish. It is also the primary cold-water fish species in China. Since the 1960s, the rainbow trout germplasm has been introduced from North Korea, the United States, Denmark, and other countries, and a systematic study has been carried out on germplasm preservation, identification, breeding, and variety breeding. Compared with rainbow trout diploid, the triploid has the advantages of a high feed conversion rate, fast growth rate, and good meat quality. Moreover, the triploid gonadal hypoplasia can mitigate risks associated with high mortality and meat quality decline during spawning and avert the ecological risk of invasive alien species caused by breeding escape. Therefore, breeding triploid rainbow trout has more significant market and ecological benefits. As diploid and triploid rainbow trout are very similar in terms of morphology, it is difficult to distinguish the ploidy of rainbow trout by morphology alone. Currently, DNA content analysis by flow cytometry is the main method used to identify the ploidy of rainbow trout, but this method necessitates the collection of fish blood or tissue samples, and the body length of the fish to collect the blood must be at least 5 cm. Additionally, these sampling operations may harm the fish. This method also involves a delicate operation, complicated technical process, and expensive consumables, thus, the popularization and application of triploid identification of rainbow trout are greatly restricted. Considering the limitations of the technical test for the ploidy of rainbow trout, a minimally invasive and economical method with only a small amount of sampling is needed to identify and analyze the ploidy of rainbow trout in batches. Microsatellite markers (SSR markers) are simple repeated sequences widely distributed in eukaryotic genomes and have been widely used in ploidy and pedigree analyses of fish. The advantages of microsatellite (SSR) analysis include high reproducibility, low sample requirements, and rapid population genetic analysis. In order to achieve the use of a minimally invasive method to collect samples for trout ploidy identification, this study analyzed 153 SSR markers using PCR amplification and electrophoresis separation technology. Among them, 139 SSR markers could be successfully amplified in diploid and triploid, and 132 SSR markers were screened for polymorphism. Finally, seven markers showed high variability in triploid. By verifying 52 reference samples with a known ploidy level and 48 samples with an unknown ploidy level, three SSR markers (SSR1054, SSR1056, and SSR1468) were further screened to distinguish the ploidy level. Moreover, three pairs of primer sequences with good stability were redesigned according to the three marker sequences for ploidy analysis application. When SSR markers were selected for ploidy identification, amplification sites with high variability were preferred because they greatly improve the efficiency of SSR-assisted ploidy identification. Differentiation of the variability of amplification sites mainly considers the number of alleles expressed and the relative frequency of these alleles. Furthermore, having clear map bands that are easy to observe and analyze is an important criterion for screening high-quality specific SSR markers. Statistical clear map bands can correctly judge the allelic configuration at each locus, thus, determining the ploidy level of rainbow trout. However, when the number of microsatellite DNA alleles shown in the electrophoretic map was less than the maximum number of alleles that may occur at the ploidy level of the polyploid species, it was difficult to accurately judge the ploidy by direct observation of the number of alleles. In diploid individuals, highly heterozygous SSR amplifies at most two alleles at a given site. Similarly, three and four alleles can be observed in triploid and tetraploid individuals, respectively. However, in some rare cases, the actual number of alleles cannot be correctly determined by looking directly at the number of alleles. For example, individuals with unknown ploidy show multiple possible genotypes for two alleles, which can occur with both diploids (AB) and triploids (AAB or ABB). Therefore, this study combined the analysis results of multiple specific SSR markers to improve the accuracy of ploidy detection. In addition, this study found three specific labeling bands that can assist in the differentiation of diploid and triploid rainbow trout, namely, SSR1054-305bp, SSR1056-463bp, and SSR1468-363bp. These three specific markers will greatly improve the accuracy of using SSR markers to identify triploid rainbow trout. Microsatellite null alleles are another potential limitation in SSR ploidy identification, which can be eliminated or avoided by changing the binding site of primers and flanking sequences due to the failure of normal gene amplification due to mutations in SSR lateral sequences. Although the results of this study cannot eliminate the presence of null alleles in future samples, the present experimental data suggest that the frequency of null alleles is so low that their impact on polyploid identification is minimal. SSR markers screened in this study solve the existing problems of a complex technical process and expensive consumables in the identification of rainbow trout ploidy, providing a minimally invasive, economical, reliable, and batch-operable molecular method and contributing to the study of the genetic diversity of rainbow trout with different ploidy.